An Analytic Hierarchy Process-based case study on older adult-friendly community therapeutic landscape design - Han, Yan; Li, Bin; Zhang, Juan (Frontiers Media SA, 2026)
With the accelerating trend of global population aging, the demand for social services among older adults continues to rise. Community therapeutic landscapes play a critical role in promoting the physical and mental well-being of older adults, fostering social interactions, enhancing living environments, and contributing to the sustainable development of communities. Grounded in Stress Reduction Theory (SRT) and Attention Restoration Theory (ART), this study identifies and synthesizes the design characteristics of therapeutic landscapes and subsequently develops an evaluation framework for community therapeutic landscape design cases. Utilizing the Analytic Hierarchy Process (AHP), a hierarchical evaluation model for therapeutic landscapes is developed, and the relative weights of key indicators are calculated. The results indicate that the Longfor Yinian Apartment Therapeutic Garden performs best in activity convenience, spatial adaptability, and social facilitation; the Elizabeth & Nona Evans Therapeutic Garden excels in natural attractiveness, exploration and interest, and environmental tranquility; and the Sun City Kobe Retirement Residence demonstrates notable strengths in environmental tranquility and natural attractiveness. Overall, contemporary community therapeutic landscape design for older adults shows stronger performance in natural attractiveness and environmental tranquility, while social facilitation remains comparatively underdeveloped. Future practice should therefore further reinforce the planning and construction of social spaces to build a more comprehensive and balanced therapeutic landscape system.